Nickel-catalyzed C–N bond reduction of aromatic and benzylic quaternary ammonium triflates. Issue 72 (17th August 2016) - Yi, Yuan-Qiu-Qiang; Yang, Wen-Cheng; Zhai, Dan-Dan; Zhang, Xiang-Yu; Li, Shuai-Qi; Guan, Bing-Tao
Abstract : A nickel-catalyzed, efficient C–N bond reduction of aromatic and benzylic ammonium triflates has been developed using sodium isopropoxide as a reducing agent. Abstract : A nickel-catalyzed, efficient C–N bond reduction of aromatic and benzylic ammonium triflates has been developed using sodium isopropoxide as a reducing agent. The high efficiency, mild conditions, and good compatibility with various substituents made this method an effective supplement to the current catalytic hydrogenation reactions. Combining this reductive deamination reaction with directed aromatic functionalization reactions, a powerful strategy for regioselective functionalization of arenes was demonstrated using dialkylamine groups as traceless directing groups.